What happens when high school students publish books? Cultural sustainability in a university – community partnership - Henningsgaard, Per (Greenleaf Publishing, 2016)
Portland State University students and faculty have trained several dozen Roosevelt High School students in editing, design, production, and marketing, as well as helped develop a curriculum that empowers high school students by giving them control of their own publishing house, Unique Ink Publishing. This particular university–community partnership is a case study that illustrates the powerful potential of “classroom publishing,” a methodology first expounded in a book of the same name published in 1992. It is also an exercise in cultural sustainability. In addition to providing vocational skill training for high school students, Unique Ink Publishing was conceived as a vehicle for the production of books that possess unique cultural value. Throughout the centuries, the book has proven to be an unparalleled format for the preservation of ideas. The student staff of Unique Ink Publishing take advantage of this capability by publishing books that preserve ideas they perceive to be underrepresented but, nonetheless, culturally valuable—something they are uniquely qualified to judge as students at one of Oregon’s poorest and most ethnically diverse high schools.